PERTIMBANGAN HAKIM MEMUTUSKAN PERKARA PERDATA MELEBIHI PERMINTAAN DALAM GUGATAN - Dela Anggrainy; Yulia Y; Teuku Yudi Afrizal (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2020)
Article 5 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power, judges are obliged to explore, follow, understand legal values and a sense of justice that live in society. Then Artticle 50 Rv, explain that the decision must not be granted beyond the demands put forward in the lawsuit. The purpose of this study is how the judge’s consideration in a lawsuit. The method in this study uses a normative juridical approach. The sesults of the study show that judging by granting more than what is being accused can be equated with illegal actions even though it is done in good faith.